Što su plesali Gogoljevi junaci - Vojvodić, Jasmina (Array, 2004)
The analysis of dance and dance techniques in Gogol's work is viewed in the framework of certain forms of corporeality as "body mechanism", "sculpturism". According to these terms, dances in Gogol's entire corpus can be divided into folk and social (i.e. ballroom) dance.